Role of maternal uncle in wedding ritual - Mumbai Archive Project Team (Jio Institute, 2024)
The mama (maternal uncle) in the family holds an important role in wedding rituals. He is entrusted with the well-being of both the bride and the groom. He may actively participate in various wedding rituals and ceremonies, offering assistance and guidance to ensure smooth proceedings and adherence.